Model-driven software engineering in practice - Brambilla, Marco, 1976-; Cabot, Jordi; Wimmer, Manuel (Morgan & Claypool Publishers, 2017)
"This book discusses how model-based approaches can improve the daily practice of software professionals. This is known as Model-Driven Software Engineering (MDSE) or, simply, Model-Driven Engineering (MDE). MDSE practices have proved to increase efficiency and effectiveness in software development, as demonstrated by various quantitative and qualitative studies. MDSE adoption in the software industry is foreseen to grow exponentially in the near future, e.g., due to the convergence of software development and business analysis. The aim of this book is to provide you with an agile and flexible tool to introduce you to the MDSE world, thus allowing you to quickly understand its basic principles and techniques and to choose the right set of MDSE instruments for your needs so that you can start to benefit from MDSE right away." - Resumé vydavatele
Keywords: softwarové inženýrství; software engineering; monografie; elektronické knihy; monographs; electronic books